THE EMERGENCE OF PHRASEOLOGY AS A FIELD OF LINGUISTIC RESEARCH - Farangis Anvarovna Temirova (Bright Mind Publishing, 2025)
This article addresses the complexity of conducting a comprehensive analysis of the origins of phraseology and providing a detailed overview of its historical development. Instead, the paper proposes a more grounded approach by outlining the key stages in the evolution of phraseology as an independent branch of linguistic science. Special attention is devoted to the study of fixed expressions within German and Swedish philological traditions, with careful consideration of the specific characteristics of the research material. The article also highlights significant issues and methodological aspects of contrastive phraseology, which merit particular scholarly attention.
Keywords: Origins of phraseology, linguistic research, key research directions, contrastive phraseology, fixed expressions.